Comparison of muscle mass and its relationship to golf performance among college amateur and professional golfers - Son, S.B.; Park, C.H.; Han, K.H.; Seo, M.K.; So, W. Y.; An, H.-S.; Sung, D.J. (Science & Sports, 2018)
Objective: The aim of this study was to compare the differences in body composition and muscle mass between golfers and non-golfers and examine a possible correlation between body composition and performance among amateur and professional golfers. Methods: The participants of the present study were 90 male colleges students and consisted of non-golfers (n=33), amateur golfers (n=31), and professional golfers (n=26). Body compositions of participants were assessed by bioelectrical impedance analysis (BIA), and golf-related performance parameters, including average round score, drive distance and putting skills, were also measured. Results: Body mass index and percentage body fat were not significantly different among the three groups. The percentage right and left arm muscle mass in the amateur (P<0.001) and professional golfers (P<0.001) were higher than that for non-golfers. The percentage trunk muscle mass in both amateur (P<0.001) and professional golfers (P<0.001) was significantly higher than that for non-golfers. Also, percentage right and left muscle mass in amateur (P<0.001) and professional golfers (P<0.001) were higher than those for non-golfers. In analysis of body composition and golf performance in amateur golfers, percentage left (P=0.044) and percentage right arm muscle mass (P=0.042) negatively correlated with average round score. Percentage left (r=0.431, P=0.020) and percentage right arm muscle mass (r=0.488, P=0.007) positively correlated with putting accuracy. Among the professional golfers, percentage trunk muscle mass negatively correlated with average round score (r=-0.510, P=0.006). In addition, percentage right arm muscle mass negatively correlated with putting accuracy (r=-0.516, P=0.010). Conclusion: These results indicate that although body compositions between amateur and professional golfers had no overall differences, regions of muscle that contributed to golf performance did differ.